(untitled) (MAUSAM, 2024)
Anthropogenic practices have been increasingly conducted on the rise in addressing the escalating demands for socioeconomic development, resulting in significant impacts on land ecosystems. This research seeks to evaluate the influence of anthropogenic activities on soil features in mountainous regions of Vietnam by focusing 84 samples collected from 12 locations across Lam River Basin at seven soil profiles (0-10, 10-20, 20-30, 30-40, 40-60, 60- 80 and 80-100 cm). The findings reveal notable differences in soil texture among land use types (LUTs). Forest cover lands (FCLs), showed the least amount of sand content, varying from 29.7% to 37.6%, while unplanted and bare lands (UBLs) had the highest sand ratios, up to 53.9%. FCLs exhibited lowest bulk density (BD), soil porosity (SP) and soil electrical conductivity (EC) and C:N ratio with respective ranges of 0.93-1.29 g.cm-3, 32.7-36.5%, 0.526-0.743 mS.m-1 and 6.74 -8.52, respectively. In contrast, crop cultivation lands (CCLs) demonstrated higher values for BD (1.17-1.25 g/cm3), SP (39.25- 43.19%), EC (0.583-0.792 mS.m-1) and C:N ratio (11.27-15.77). UBLs, on the other hand, exhibited even highest values up to 1.23-1.36 g.cm-1, 43.19-49.62%, 0.437-0.619 mS.m-1 and 11.68-16.58% and displayed high levels of exchange irons and soil organic content compared to FCLs. Other factors such as pH varied little in space between the sampled soil locations and along the soil profiles. Overall, the study indicates that anthropogenic practices have impacts on the soil features across the study area.